Reform of the EU common market organisation for fruit and vegetebles - Čačić, Jasna (Array, 2009)
A new Common Market Organisation (CMO) for fruit and vegetables is in place from 1 January 2008. First debate about reform was lunched in 2004 by European Commission and its publication about simplification of the Fruit and Vegetable Common Market Organisation. The last extensive reform in 1996 introduced modifications like a plan for the progressive reduction of support for short-term market intervention and the strengthening of structural aid to improve competitiveness in order to help producers to develop their capacity and to adapt to market demand. The most important reasons for the new reform of CMO for fruit and vegetables are imbalance in the supply and distributions chain, limited influence of the producers’ organisations, coherence with rural development aid and the questions of standards